ISOLATION AND CHARACTERIZATION OF CHITOSAN NANOPARTICLES FROM CRAB SHELL WASTE (PORTUNUS PELAGICUS) - YUSAN, LIZA YUDISTIRA; NAILUFA, YUYUN; SUBAGIO, HARI (International Journal of Applied Pharmaceutics, 2024)
Objective: The purpose of this study was to isolate and characterize of chitosan nanoparticles derived from Portunus pelagicus shell waste. Methods: Chitosan was isolated by deproteination, demineralization, and deacetylation methods. Furthermore, nanoparticles (NPs) were made by the ionic gelation method by dissolving chitosan in a mixture of acetic acid and sodium tripolyphosphate. The particle size analyzer and Fourier Transform Infrared Spectroscopy were used to measure the particle size of NPs and determine the functional group and degree of deacetylation. Results: The yield percentage of chitosan was 90.7%. The size of chitosan nanoparticles based on the highest intensity is 15.05 nm with a polydispersity index (PDI) value of 0.1140 at a concentration of 1%. Based on the degree of deacetylation of chitosan nanoparticles, it was found to be 84.98% at 1% concentration. Conclusion: The conclusion of this study is the formation of chitosan nanoparticles (1-100 nm) isolated from Portunus pelagicus shell waste. Based on the degree of deacetylation, chitosan nanoparticles with high chitosan content (>75%) were obtained.